The predictive role of tertiary lymphoid structures in the prognosis and response to immunotherapy of lung cancer patients: a systematic review and meta-analysis - Xin Liu; Wu Lv; Danxue Huang; Hongxia Cui (BMC Cancer)
Abstract Background There is still no consensus regarding the correlation between TLS and the prognosis of lung cancer patients. This meta-analysis aimed to investigate the association between TLS and prognosis in patients with lung cancer. In addition, the prognostic value of TLS for the efficacy of immunotherapy was also studied. Methods We systematically searched the PubMed, Embase, Cochrane Library, and Web of Science databases from database inception to November 1, 2023. The hazard ratio (HR) and corresponding 95% confidence interval (CI) for overall survival (OS), disease-free survival (DFS), recurrence-free survival (RFS), progression-free survival (PFS) and disease-specific survival (DSS) were extracted and merged with STATA 14.0. The study protocol was registered with PROSPERO (CRD42024502483). Results A total of 17 studies comprising 4291 patients were included in this meta-analysis. The pooled results revealed that high TLS/TLS + patients had better OS (HR = 0.66, 95% CI: 0.50–0.88), DFS (HR = 0.46, 95% CI: 0.33–0.64), DSS (HR = 0.48, 95% CI: 0.39–0.60) and RFS (HR = 0.43, 95% CI: 0.33–0.57). High TLS/TLS + patients tended to have longer PFS than low TLS/TLS + patients (HR = 0.68, 95% CI: 0.35–1.35). Interestingly, in the Asia subgroup, the association between TLS and survival was especially significant, whereas there was no significant difference in Europe. In addition, in patients who received neoadjuvant chemoimmunotherapy, high TLS/TLS + was associated with prolonged DFS (HR = 0.21, 95%CI: 0.05–0.93). Conclusion High TLS/TLS + was associated with improved survival and an improved response to neoadjuvant chemoimmunotherapy in lung cancer patients, suggesting that TLS may be a prognostic biomarker and may also be a promising predictive marker for the response to neoadjuvant chemoimmunotherapy. However, additional original studies are needed to further confirm these findings.